(untitled) (GESTIÓN Y TENDENCIAS, 2019)
The relevance of the gender perspective for the world of work lies in the contributions it makes to the discussion of, and reflection on, the most varied practices of organizational and labor management. These contributions invite us to think of gender not as something one is, but as something one does. Gender is therefore a concept that does not only denote a social construction, a binary identity and its images; gender is also an analytical category —in other words, a way of speaking about power. What this special issue invites us to consider is a perspective entailing an analysis of the organizational practices that sustain the division of labor between the sexes. In other words, its use in organizations affords a sensitivity to the contradictions and ambiguities present in gender relations and in what is considered discrimination and equal opportunity at work.